Schismatothelinae spiders (Araneae, Mygalomorphae, Theraphosidae) from Colombia: four new species and an approach to their diversity - Valencia-Cuéllar, Dayana; Perafán, Carlos; Guerrero, Roberto J.; Guadanucci, José Paulo Leite (Zootaxa, 2019)
The spider subfamily Schismatothelinae from Colombia is revised. One new species of Euthycaelus Simon 1889 and three new species of Schismatothele Karsch 1879 are named, as well as new geographical records provided. E. guane sp. nov. from Santander, S. hacaritama sp. nov. from Norte de Santander, S. olsoni sp. nov. from Norte de Santander and Táchira (Venezuela), and S. weinmanni sp. nov. from Cundinamarca are herein described, diagnosed and illustrated. Schismatothele is newly recorded from Colombia. Morphological aspects and diversity of the Ischnocolinae and Schismatothelinae from Colombia are discussed. An identification key to species of these subfamilies from Colombia is provided.